2014
DOI: 10.1158/1940-6207.capr-13-0405
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Active Site Peptide Analog of α-Fetoprotein That Prevents Breast Cancer

Abstract: Epidemiologic studies associate elevated maternal serum levels of a-fetoprotein (AFP) with reduced breast cancer risk for parous women. Laboratory studies demonstrate direct anti-breast cancer activity of AFP. Here, we review the development of a small cyclic peptide that is an active site analog of AFP, referred to as AFPep, which is composed exclusively of amino acids, is orally active, has no discernable toxicity, and is effective for the treatment and prevention of breast cancer in animal models. Cancer Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…11 , 12 In addition, the maternal serum alpha-fetoprotein (AFP) level was high during pregnancy, and the AFP had direct antibreast cancer activity. 13 , 14 Therefore, the age at diagnosis of breast cancer increased with increased parity. Albrektsen et al 15 found that women with multiparity had a slightly lower risk of breast cancer compared with women with parity 1.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 12 In addition, the maternal serum alpha-fetoprotein (AFP) level was high during pregnancy, and the AFP had direct antibreast cancer activity. 13 , 14 Therefore, the age at diagnosis of breast cancer increased with increased parity. Albrektsen et al 15 found that women with multiparity had a slightly lower risk of breast cancer compared with women with parity 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the enzyme active site is considered, its role in cancer is also dependent on the feature of the protein (oncogene or tumor suppressor gene). For example, in breast cancer, overexpression of BCRP (breast cancer resistance protein) with its intact active site could cause drug resistance, while mutation in the active site of α-fetoprotein (AFP) could reduce breast cancer risk 46 . These mutations can impact enzymes to metabolize different substrates 47 , leading to pathological processes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reason for the high levels of AFP when a diagnosis of breast cancer is established and other diseases are ruled out remains unexplained. Although studies have shown that AFP has endocrine effects that may reduce the risk of estrogen-dependent breast cancer ( 14 ), it is obviously not applicable to this patient. If we assume that the occurrence of PNECB promoted AFP secretion, then AFP levels should have declined at the postoperative assessment points; yet, there was no reduction in post-treatment AFP levels.…”
Section: Discussionmentioning
confidence: 99%